Avaliação do conceito bolha como critério de compensação ambiental em atividades poluidoras do ar atmosférico - estudo de caso no Estado de São Paulo - Santos, Elio Lopes dos (2004)
The present study was an evaluation of the Bubble Concept a environmental criterium of compensation used by the United States Environmental Protection Agency and by the Environmental Agency of the CETESB in Cubatão, to regulate the implantation of new industrial enterprises and its amplifications. Studies ware done refering to the environmental licensing of the following industrial enterprise in the São Paulo State: Central of Energy Generatin of Santos lowland with the proposal of implantation in the area of the President Bernard s refinery in the Cubatão; Central of Energy Generation Carioba II, with the proposal of the implantation in the Americana town and a factory of Carbon Black, implanted in Paulínia. A bibliographic survey that included the scientific literature, that included national and international entities of research, Environmental Law of São Paulo State and Federal Environmental Law. In the stage of the interview technicians of the industries technicians of the Company of the Technology of Environmental Sanitation of São Paulo State were listened. Environmental Consultants, students of Pos-Graduation and Environmental Management of Santa Cecilia University, Justice Prosecutors and people of no governmental Organizations. It was concluded that the absence of criterium or even the use of criterium of environmental compensation with basis in the Bubble Concept founded in the exchange of pollutants in the proportion of 1:1 does not promote the improvement and the recovery of the quality of the air of the Regions and Sub-Regions saturated of atmospheric pollutants or in ways of saturation, contraposing itself to the Federal Law n. 6938. As an alternative to make the implantation of the new industrial enterprises or enlargements possible, with the improvement and recuperation of the air quality in Regions and Sub-Regions saturated of atmospheric pollutants this paper suggests several alterations in the Bubble Concept .